Integrasi Game Gcompris Dalam Kurikulum PAUD untuk Meningkatkan Early English Literacy Skills - Gustina, Lida Hani; Zulkarnain, Riski; Alimningtyas, Wahyu Nur; Angrawaty, Nunung; Limantoro, Gray Hansen (Paedagogie, 2026)
The development of early English literacy in early childhood education continues to present significant pedagogical challenges, particularly in designing instructional methods that are both engaging and developmentally appropriate. This study aims to analyze the effectiveness of integrating GCompris—an open-source educational game platform—into the early childhood education (ECE) curriculum to enhance early English literacy skills. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart spiral model, implemented across three learning cycles over a 12-week period. A total of 32 children aged 5–6 years from an ECE learning group in Balikpapan participated in the study. Four dimensions of early English literacy were assessed: alphabet recognition, basic vocabulary acquisition, simple phonetic awareness, and picture-word comprehension. Twelve GCompris activities were systematically integrated into the curriculum by applying multisensory approaches, gamification principles, and adaptive self-directed learning strategies. The findings revealed a highly significant improvement in mean scores of 60.90%, from a pre-test score of 48.75 to a post-test score of 78.44. Simple phonetic awareness recorded the highest percentage gain (67.24%), followed by basic vocabulary acquisition (65.04%), alphabet recognition (57.03%), and picture-word comprehension (55.87%). Student active participation increased from 68.75% in Cycle I to 93.75% in Cycle III. Qualitative findings derived from teacher and parent interviews confirmed notable improvements in motivation, self-confidence, and spontaneous use of English outside the classroom. The novelty of this study lies in the empirically validated GCompris integration model developed across three cycles, which demonstrated the capacity to simultaneously enhance multiple dimensions of literacy. These findings provide an evidence-based framework for technology-assisted foreign language learning, with significant implications for early childhood curriculum development and teacher professional training.